Maximum Limitation of Fines for Economic Crimes In Law Number 1 of 2023 - Herman, Herman; Fernhout, Fokke J. (Magister of Law, Faculty of Law, University of Mataram, 2023)
Criminal law provisions in the colonial-era Criminal Code are no longer competent to uphold society’s sense of justice due to the emergence of more sophisticated crimes with a variety of modus operandi. By approving Law Number 1 of 2023 on the Criminal Code, the first steps toward reforming the criminal code were taken. One of the recently established law reforms has to do with the criminal justice system. In this study, the punishment scheme in Law Number 1 of 2023 will be identified and analyzed, as well as the effects of the law’s provision for maximum criminal sentences for economic offenses. This article’s study was conducted using a normative legal research methodology that included statutory, conceptual, and case-based approaches. The study’s findings demonstrate that Law Number 1 of 2023 offers minimal and maximum protections against criminal risks, among them economic crimes. If the loss resulting from the offense exceeds the maximum fine that may be imposed, this rule may result in unfairness, especially for the victim. Additionally, because judges are not allowed to impose sentences that exceed the predetermined guidelines, the maximum punishment cap may lessen the deterrent effect on criminals.